Freeze casted porous ceramics (2020)
Scientists have explored different manufacturing methods aiming at obtaining synthetic materials with controlled porosity, among them, Freeze Casting allows a control of the pore characteristics formed within the material by setting process variables like type of medium, particle size, solid content, inclusion of additives, freezing rate, etc. Despite of all the knowledge obtained about freeze casting, there still remain some questions to solve regarding processing-structure relationships, specifically the relations between cooling patterns during freezing and physical characteristics of the final material. The aim of this doctoral work is to understand the relations between cooling patterns during freezing and the structure at the macro and micro levels of the final freeze casted part. The current work comprises the development of a heat transfer model to efficiently and reliably predict the temperature evolution during freezing. In this way, it will be possible to recognize which are the process variables affecting the final pore morphology. The results of this work improved the fundamental knowledge of the process, serving as a tool to predict and control the microstructure obtained in the Freeze Casting process. The problem definition and goals of this work are presented in chapter 1. A brief description of the main literature on freeze casting is presented in chapter 2. The development of a numerical model that calculates the temperature distribution within the experiment domain was carried out in chapter 3. In chapter 4, an alumina tile was produced by freeze casting process in order to test the freezing device, coloidal suspension characteristics and sintering temperature of the sample. Additionally, an analytical model was proposed for predicting the thermal conductivity of the material. Chapter 5 evaluates the effect of solid content and freezing temperature on pore morphology and evaluates how these variables affect the temperature distribution within the experiment domain. Chapter 6 compares the steady solution of the numerical model and the pore morphology obtained experimentally under different process parameters. Finally, conclusions and future work for the study are presented in chapter 7.